Sikap dan Praktik Pemberian Susu Formula pada Bayi Usia 6 Bulan sampai dengan 2 Tahun - Hilda Yani Karo Karo (EMBRIO, 2020)
Lifestyle development and patterns of providing nutrition to children continue to develop in line with the times. One of the patterns of providing these nutrients is formula milk or non-breast milk which is favored by some parents. Actually, when viewed from the side of health, formula milk is no more than breast milk. That is because instant milk or formula milk contains added sugar. Babies who consume formula milk are more likely to experience diarrhea, respiratory infections, obesity and diabetes later in life than babies who consume breast milk. This type of research is descriptive with cross sectional approach, namely data collected at that time which aims to determine the behavior of mothers towards formula feeding at the age of 6 months to 2 years at the Wifa clinic in Medan. The population in this study were mothers who came to the Wifa Medan clinic who provided formula milk at the age of 6 months to 2 years as many as 30 people. Sampling using Accidental sampling. The results showed that knowledge of mothers who are well-knowledgeed are 9 people (30%), have enough knowledge of 15 people (50%), and lack knowledge of 6 people (20%). The majority of mothers who give formula milk at the age of 6 months to 2 years have a positive attitude of 11 people (36.67%) and some have a negative attitude of 19 people (63.33%).